2018
DOI: 10.1017/s0714980818000041
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Inventory of Attitudes Toward Seeking Mental Health Services (Chinese Version)

Abstract: Research on underutilization patterns of mental health services among older Chinese immigrants is limited, partly due to the absence of translated, psychometrically sound measures for assessing attitudes towards seeking help. In this study we interviewed 200 older Chinese Canadian immigrants using a translated version of the Inventory of Attitudes Toward Seeking Mental Health Services scale (IASMHS), and assessed mental health care utilization over the past 12 months and intentions to seek help. Confirmatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The IASMHS was subjected to EFA, validating a three-factor structure, comprised of the following dimensions: help-seeking propensity, indifference to stigma and psychological openness. These results not only corroborated the original study of the inventory (Mackenzie et al 2004) but also the Portuguese study (Fonseca et al 2017) as well as numerous other international studies (e.g., Hyland et al 2014;Kantor et al 2017;Tieu et al 2018).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The IASMHS was subjected to EFA, validating a three-factor structure, comprised of the following dimensions: help-seeking propensity, indifference to stigma and psychological openness. These results not only corroborated the original study of the inventory (Mackenzie et al 2004) but also the Portuguese study (Fonseca et al 2017) as well as numerous other international studies (e.g., Hyland et al 2014;Kantor et al 2017;Tieu et al 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Item 23 loaded on the help-seeking propensity factor, which was not expected, however it was retained for exhibiting adequate characteristics. The reduction of the scale to 20 items has already been observed in other studies (Tieu et al 2018;Tuliao et al 2019). Regarding the items with limitations, it is observed that these seem to be constant in the literature (Kantor et al 2017;Tieu et al 2018;Tuliao et al 2019) since items 1, 4, 7 and/or 14 have frequently been shown to be problematic and item 23 has often revealed factor loading problems.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations